Gramsci e un bilancio (preventivo) dell’esperienza rivoluzionaria a Torino - Silvestrini, Flavio (International Gramsci Journal, 2023)
Gramsci: a (Provisional) Balance-sheet of the Revolutionary Experience in Turin. Gramsci’s report on the 1919-1920 council movement in Turin, here published for the first time in its original Italian, may fairly be said to represent a phase of passage in the (intellectual) biography of the young Sardinian. In particular, there are four interpretative elements that allow us to put the importance of this process in perspective. First, there is the balance-sheet he draws up of the Italian revolution and its possible developments; then, there is his re-evaluation of the role of the Party within a systematic theory of proletarian institutions; next, we see the theoretical-practical link-up with the top leadership of the Communist International; Gramsci specifies his own position both inside and, finally, outside the maximalist current in the light of the republication of the article in “L’Ordine Nuovo”, in its form as a daily paper, in March 1921.